The need for hands-on training and supervision for entry-level physicians in a country with low surgical staffing density: a nationwide survey in Ghana - Mee Joo Kang; Reuben Kwesi Sakyi Ngissah; Alexis Dun Bo-Ib Buunaaim; Richard Baidoo; Francis Odei-Ansong; Theodore Wordui; Ernest Kwame Adjepong-Tandoh; Paa Kwesi Baidoo; James Emmanuel Kwegyir Aggrey-Orleans (BMC Medical Education, 2023)
Abstract Background Despite the largely unmet need, relatively few medical school graduates enrol in surgical residency and fewer surgical specialists work rurally in low- and middle-income countries. Surgical housemanship is the only formal training for medical graduates who will become the main surgical care providers in underserved areas. This study aimed to evaluate Ghanaian surgical housemanship (internship) and its impact on independent medical practice. Methods A nationwide questionnaire survey of surgical trainees from seven teaching or regional-level hospitals ascertained the experience and self-confidence levels for 35 training objectives set by the Medical and Dental Council of Ghana, and suggestions to improve surgical training quality. Results Of 310 respondents, 59.7% experienced ≤ 10 cases for each topic, and 24.8% reported self-confidence as ≤ 2 points (out of 5). More than 90% of respondents experienced ≤ 10 cases for gastric, colorectal and liver cancer management. Teaching hospital trainees had lower proportions of those experiencing > 10 cases (36.6% versus 43.7%) and reporting self-confidence ≥ 4 (46.5% versus 55.8%), respectively, compared with those from regional/other-level hospitals. 40% of respondents were not confident about their surgical skills, and 70.5% requested better-supervised and practical surgical skills training. The proportion of respondents who reported limited supervision was higher among those from teaching hospitals, reported self-confidence scores < 4, and experienced ≤ 10 cases for each topic. 67% of respondents were satisfied with their surgical housemanship and 75.8% perceived surgical rotation as relevant to their future work. Conclusions Most surgical trainees are concerned about their surgical skills. A structured curriculum with specific goals and better-supervised surgical skills training should be established. Inclusion of regional/other-level hospitals in surgical training may reduce the supervisory burden in teaching hospitals.